Influence of the detection of parent-of-origin on the pregnancy outcomes of fetuses with copy number variation of unknown significance - Chen, Lin (Sci Rep, 2020)
The widespread application of high-resolution chromosome detection technology in clinical practice has identified many variants of unknown significance (VOUS) in prenatal diagnosis. The purpose of this study was to prospectively analyze the chromosomal results of parents and the follow-up information of pregnancy outcomes of prenatal samples with VOUS, so as to determine the influence of the detection of parent-of-origin on the pregnancy outcomes of fetuses with VOUS. The present study analyzed amniotic fluid samples obtained from women with different risk indications between February 2017 and December 2018. The samples were subjected to copy number variation sequencing, and detection of parent-of-origin was suggested in cases of samples with VOUS. The pregnancy outcome was followed up. In a total of 14073 amniotic fluid samples, 729 cases of VOUS were detected (5.2%, 729/14073) and 721 cases were followed up successfully. Among the 721 cases, 525 patients agreed to detect the parent-of-origin (72.8%, 525/721). It was revealed that the VOUS in 460 of the fetuses were hereditary (87.6%, 460/525). The percentages of abnormal pregnancy outcomes (included pregnancy loss, fetal pathological abnormality, preterm delivery, neonatal death, birth defects) in the inherited, de novo, and refusal to detect the parent-of-origin (i.e. unknown origin) groups were 4.3% (20/460), 6.2% (4/65), and 6.6% (13/196), respectively. There was no significant difference among the three groups (P > 0.05). The rate of voluntary termination of pregnancy (TOP) in the unknown origin group was significantly higher than that in the group that had determined the parent-of-origin (14.3% vs 7.4%, P = 0.005). There is currently no evidence that suggests that the proportion of abnormal pregnancy outcomes is higher in fetuses with VOUS than in other fetuses. However, the present study revealed that determining the parent-of-origin affects the decision to undergo voluntary TOP, as the rate of voluntary TOP in the group that refused detection was higher than that in the group that consented.